2015
DOI: 10.1590/s1678-86212015000400048
|View full text |Cite
|
Sign up to set email alerts
|

Um estudo sobre as causas de aumentos de custos e de prazos em obras de edificações públicas municipais

Abstract: Resumodesempenho deficiente de obras públicas em relação aos aumentos de custos e prazos de entrega, em comparação com os valores previstos, tem sido recorrente no Brasil e outros países emergentes. Diversos estudos têm concentrado atenção na análise de causas desses desvios, bem como de possíveis diretrizes para a garantia do desempenho dos empreendimentos. O presente trabalho apresenta um estudo diagnóstico sobre o aumento de custos e prazos de obras públicas de edificações em Belo Horizonte. Inicialmente, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
(13 reference statements)
2
2
0
11
Order By: Relevance
“…Studies presented in various articles indicate that the problem of cost increase is common to several countries and that the causes are recurrent. The poor performance of public works in relation to cost increases and delivery times, compared to expected values, has been recurrent in Brazil and other emerging countries (Santos et al, 2015). Santos et al (2015) [1] in a study on the causes of cost increases and deadlines in municipal public building works in Belo Horizonte concluded that 72% of the 145 works evaluated presented a cost increase, very similar with this present study in which 71% of 238 contracts under study showed a cost increase.…”
Section: Literature Reviewsupporting
confidence: 85%
See 1 more Smart Citation
“…Studies presented in various articles indicate that the problem of cost increase is common to several countries and that the causes are recurrent. The poor performance of public works in relation to cost increases and delivery times, compared to expected values, has been recurrent in Brazil and other emerging countries (Santos et al, 2015). Santos et al (2015) [1] in a study on the causes of cost increases and deadlines in municipal public building works in Belo Horizonte concluded that 72% of the 145 works evaluated presented a cost increase, very similar with this present study in which 71% of 238 contracts under study showed a cost increase.…”
Section: Literature Reviewsupporting
confidence: 85%
“…The poor performance of public works in relation to cost increases and delivery times, compared to expected values, has been recurrent in Brazil and other emerging countries (Santos et al, 2015). Santos et al (2015) [1] in a study on the causes of cost increases and deadlines in municipal public building works in Belo Horizonte concluded that 72% of the 145 works evaluated presented a cost increase, very similar with this present study in which 71% of 238 contracts under study showed a cost increase. Santos et al still present in their study that the two most important causes regarding the delay of the works are related to the lack of compatibility of the projects and error in the quantitative survey.…”
Section: Literature Reviewsupporting
confidence: 85%
“…Conforme se observa na literatura, os projetos de AE são apontados como itens preponderantes para assertividade nos custos de empreendimentos imobiliários (MUIANGA; GRANJA; RUIZ, 2015;NEVES et al, 2017;SANTOS;STARLING;ANDERY, 2015). Nesse contexto, o TVD apresenta-se como uma possibilidade de discutir processos de integração e reflexões sobre o valor em projetos de empreendimentos públicos.…”
Section: unclassified
“…Dessa maneira, existe a possibilidade de que os processos de reabilitação nessas obras sejam feitos de maneira ineficiente, negligenciando fatores importantes ou não sendo executados plenamente. O setor de construção gasta muitos recursos públicos, é inconcebível que obras reabilitadas necessitem de mais recursos e novas intervenção devido a procedimentos inadequados (Santos et al, 2015;Campelo e Cavalcante, 2013). Sendo assim, observa-se dois pontos relevantes que necessitam de maiores investigações quanto aos seus procedimentos e aplicações sendo eles: as obras de reabilitação e as obras públicas.…”
Section: Introductionunclassified